Resource Sharing in Libraries on Cloud Landscape: Potentials and Paradoxes - Mayank Yuvaraj (International Journal of Informatics and Communication Technology (IJ-ICT), 2015)
The initial hype of any development can eclipse its practical applications. The present paper attempts to separate the hype of cloud computing and explores the possibilities of resource sharing in libraries through Cloud Computing. The present study is based on the usage pattern of cloud computing in libraries and explores a model for resource sharing. It also proposes a cloud based resource sharing framework for moving from ground to the cloud. Although a lot of work has been done on cloud computing yet none of the works has been dedicated to the cause of libraries. With the development of electronic resources and shift in user’s preference of online services there is an urgent need of change in library practices.